A new briarane diterpene, briarlide S from Okinawan soft coral pachyclavularia violacea - Misaki Nagasaka; Kazuki Tani; Masahiro Wada; Miyu Wakatsuki; Ng, Shean Yeaw; Takahiro Ishii (Springer Nature, 2023)
A new briarane diterpene, briarlide S (1), six known compounds, briarlides A, B, E, G, and H (2–6), and brianodin B (7) were isolated from the soft coral, Pachyclavularia violacea, collected from the coast of Apogama, Okinawa prefecture. Chemical structures of the isolated compounds were elucidated by FTIR, NMR, and HR-ESI-MS analyses. The relative stereochemistry of 1 was determined using NOESY. The isolated compounds 1–7 were evaluated for antibacterial activity and brine shrimp toxicity.